Is long‐acting reversible contraceptive method use associated with HIV testing frequency in KwaZulu‐Natal, South Africa and Lusaka, Zambia? Findings from the CUBE study - Mags Beksinska; Alice F. Cartwright; Jennifer Smit; Margaret Kasaro; Jennifer H. Tang; Maria Fawzy; Virginia Maphumulo; Manze Chinyama; Esther Chabu; Rebecca Callahan (Contraception: X, 2023)
Objectives: To assess differences in HIV testing at 6-months intervals over 24 months among intramuscular depot medroxyprogesterone acetate (DMPA-IM) injectable, levonorgestrel implant, or copper intrauterine devices (IUD) users in KwaZulu-Natal, South Africa, and Lusaka, Zambia. Testing at recommended intervals has not been previously assessed in long-acting reversible contraceptive (LARC) users (implant and IUD users) compared to those using effective but shorter-acting methods (such as DMPA-IM) in sub-Saharan Africa. Study design: As part of the longitudinal contraceptive use beyond ECHO (CUBE) study, we measured HIV testing over 24 months. Participants were considered continuous users of DMPA-IM, levonorgestrel implant, or copper IUD if they used the same method across all months of their study participation, or not continuous users of their baseline CUBE method if they switched or discontinued their method. We used multivariable logistic regression models with generalized estimating equations and robust standard errors, stratified by country, to assess differences in HIV testing. Results: Among the 498 participants, HIV testing rates were higher in Zambia for all methods compared to South Africa. In bivariate analyses, continuous implant or IUD users (the LARC users) were significantly less likely to report having received HIV testing at the 6-months and 24-months surveys, compared to continuous DMPA-IM users. In adjusted longitudinal models, continuous IUD users (adjusted odds ratio: 0.42, 95% CI: 0.24, 0.74), continuous implant users (adjusted odds ratio: 0.23, 95% CI: 0.12, 0.42) in South Africa had significantly lower odds of HIV testing compared to continuous DMPA-IM users. There were no significant differences in Zambia in the adjusted models. Conclusion: LARC use may reduce opportunities for HIV testing and users should be counseled on regular HIV testing and the option of HIV self-testing. Implications: Due to infrequent clinical contacts which may lead to lower rates of HIV testing at recommended intervals, LARC users should be provided opportunities to test for HIV at home or when seeking other health services.